Correlations between serum laminin level and severity of heart failure in patients with chronic heart failure - Xie, Ling; Zhou, Zhen; Chen, Hai-Xiao; Yan, Xiao-Yun; Ye, Jia-Qi; Jiang, Ying; Zhou, Lei; Zhang, Qing (Frontiers in Cardiovascular Medicine, 2023)
Objective This study aimed to investigate the correlation between serum laminin (LN) levels and clinical stages of heart failure in patients with chronic heart failure. Methods A total of 277 patients with chronic heart failure were selected from September 2019 to June 2020 in the Department of Cardiology, Second Affiliated Hospital of Nantong University. Based on stages of heart failure, the patients were divided into four groups: stage A, stage B, stage C, and stage D, with 55, 54, 77, and 91 cases, respectively. At the same time, 70 healthy people in this period were selected as the control group. Baseline data were recorded and serum Laminin (LN) levels were measured. The research compared, the differences in baseline data among the four groups of HF and normal controls, and analyzed the correlation between N-terminal pro-brain natriuretic peptide (NT-proBNP) and left ventricular ejection fraction (LVEF). The receiver operating characteristic (ROC) curve was used to evaluate the predictive value of LN in the C-D stage of heart failure. Logistic multivariate ordered analysis was applied to screen the independent related factors of clinical stages of heart failure. Results Serum LN levels in patients with chronic heart failure were significantly higher than those in healthy people, which were 33.2 (21.38, 101.9) ng/ml and 20.45 (15.53, 23.04) ng/ml, respectively. With the progression of clinical stages of HF, serum LN and NT-proBNP levels increased, while LVEF gradually decreased (P < 0.05). Correlation analysis showed that LN was positively correlated with NT-proBNP (r = 0.744, P = 0.000) and negatively correlated with LVEF (r = −0.568, P = 0.000). The area under the ROC curve of LN for predicting C and D stages of heart failure was 0.913, 95% confidence interval was 0.882–0.945, P = 0.000, specificity 94.97%, and sensitivity 77.38%. Multivariate Logistic analysis showed that LN, Total bilirubin, NT-proBNP and HA were all independent correlates of heart failure staging. Conclusion Serum LN levels in patients with chronic heart failure are significantly increased and are independently correlated with the clinical stages of heart failure. It could potentially be an early warning index of the progression and severity of heart failure.